2018
DOI: 10.1186/s40168-018-0451-2
|View full text |Cite
|
Sign up to set email alerts
|

Multi-cohort analysis of colorectal cancer metagenome identified altered bacteria across populations and universal bacterial markers

Abstract: BackgroundAlterations of gut microbiota are associated with colorectal cancer (CRC) in different populations and several bacterial species were found to contribute to the tumorigenesis. The potential use of gut microbes as markers for early diagnosis has also been reported. However, cohort specific noises may distort the structure of microbial dysbiosis in CRC and lead to inconsistent results among studies. In this regard, our study targeted at exploring changes in gut microbiota that are universal across popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
339
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 399 publications
(360 citation statements)
references
References 51 publications
19
339
2
Order By: Relevance
“…The association of microbiota with the adenoma‐adenocarcinoma pathway has been the subject in several recent studies. Patients with invasive CRC have been consistently described with higher RA of Fusobacterium when compared to healthy controls . However, differences in the RA of Fusobacterium and other microbiota between healthy controls and patients with adenomas is less consistent.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The association of microbiota with the adenoma‐adenocarcinoma pathway has been the subject in several recent studies. Patients with invasive CRC have been consistently described with higher RA of Fusobacterium when compared to healthy controls . However, differences in the RA of Fusobacterium and other microbiota between healthy controls and patients with adenomas is less consistent.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with invasive CRC have been consistently described with higher RA of Fusobacterium when compared to healthy controls. 3 However, differences in the RA of Fusobacterium and other microbiota between healthy controls and patients with adenomas is less consistent. There is evidence both for and against such differences.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This study suggested that P. anaerobius directly interacted with colonic epithelial cells and also promoted CRC by modifying the tumor immune microenvironment. While the causal role of the species Parvimonas micra (P. micra) has not been biologically validated, multiple clinical studies reported an elevated level of P. micra in CRC patients Yu et al (2017); Purcell et al (2017); Dai et al (2018). Of interest, Parvimonas were closely associated with animal-based diets, which have previously been shown to be significantly associated with increased risk for CRC Chan et al (2011).…”
Section: Analysis Of Microbiome Data From Colorectal Cancer Patientsmentioning
confidence: 99%